Design and Analysis of Grid Connected Photovoltaic Rooftop System in the Kadudampit District Office - Edwinanto; Yudha Putra; Harurikson Lumbantobing; Yufriana Imamulhak; Danial Zulfiqar (Universitas Nusa Putra, 2023)
Utilizing clean and renewable energy is crucial for progress and development. Reducing carbon emissions is the goal of using this renewable energy, resulting in a clean and healthy environment. With only a tiny CO2 emission of 20.32% or CO2 emissions reduced by up to 79.69%, solar energy is regarded as one of the most environmentally friendly renewable energy sources. The method used in this study is to simulate the creation of PLTS with the HelioScope web application with a design project for the Kadudampit sub-district office, Sukabumi district. The results of this study are that with the use of new renewable energy (EBT) for solar power plants (PLTS), the monthly energy production obtained is relatively stable, with yields ranging from 1,041.5 kWh - 1,568.1 kWh, and the annual energy production got is 14,853.7 kWh.